2016
DOI: 10.1007/s40520-016-0606-6
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of neurology specialists toward older adults

Abstract: Generalization of geriatrics education may translate into a better understanding and improved care for older patients. Development of instruments and implementation of qualitative studies to assess attitudes of neurologists toward older adults are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
1
6
1
2
Order By: Relevance
“…However, it should be pointed out that the 77% with positive attitudes had more contact with disciplines in the field of geriatrics. 8 This disinterest of health professionals and students may be the result of the lack of disciplines focusing on geriatrics and gerontology in undergraduate courses, which contrasts with policies for elderly care. 9,10 Difficulties in dealing with situations of abandonment, death and dependence, communication problems during appointments and the larger number of treatments that these patients undergo in comparison to young adults are also factors that likely exert an influence on such attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be pointed out that the 77% with positive attitudes had more contact with disciplines in the field of geriatrics. 8 This disinterest of health professionals and students may be the result of the lack of disciplines focusing on geriatrics and gerontology in undergraduate courses, which contrasts with policies for elderly care. 9,10 Difficulties in dealing with situations of abandonment, death and dependence, communication problems during appointments and the larger number of treatments that these patients undergo in comparison to young adults are also factors that likely exert an influence on such attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Uğurlu et al 104 determined that the attitudes of healthcare workers toward the elderly are generally positive 104 . Other research has revealed that doctors and nurses have positive attitudes toward the elderly 21,105‐111 . The fact that the general conclusion in research conducted in Turkey is that healthcare workers have positive attitudes toward elderly individuals may originate from the appearance of the elderly as individuals who are valued, wise, and respected by society.…”
Section: Discussionmentioning
confidence: 99%
“…104 Other research has revealed that doctors and nurses have positive attitudes toward the elderly. 21,[105][106][107][108][109][110][111] The fact that the general conclusion in research conducted in Turkey is that healthcare workers have positive attitudes toward elderly individuals may originate from the appearance of the elderly as individuals who are valued, wise, and respected by society. It has reported that elderly individuals are generally accepted as a burden to society, 112 are generally identified with negative concepts, such as unproductive and useless, and for this reason suffer discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…Yapılan çalışmalarda bulgularımıza benzer şekilde doktorların ve hemşirelerin yaşlı ayrımcılığına karşı tutumların olumlu olduğu bulunmuştur. (4,18,22,23) . Ögenler (13) Yakın zamanda yapılan bir araştırmada hemşirelerin yaşlılara karşı tutumlarının düşük düzeyde pozitif olduğu saptanmıştır.…”
Section: Discussionunclassified
“…Sınırlı sayıda klinik alanda da çalışmalar bulunmakla birlikte birinci basamak sağlık hizmetleri düzeyinde çalışmalar sınırlıdır. (12,13,14,15) Sağlık çalışanlarının yaşlı bireylere karşı olumsuz tutumlara sahip olduklarını gösteren çalışmalar bulunduğu gibi (3,8,15,16) olumlu tutumlara sahip olduklarını gösteren çalışmalar (4,17,18,19) , hem olumlu hem olumsuz tutumlarının olduğunu bildiren araştırmalar da vardır. (9) Bu çalışmada, Aile Sağlığı Merkezi (ASM) sağlık çalışanlarının yaşlı ayrımcılığına ilişkin tutumlarının belirlenmesi amaçlanmıştır.…”
Section: Introductionunclassified